Efektivitas sampah organik sebagai adsorben logam kromium (Cr) dalam limbah cair industri tekstil: sistematika reviu - ‘Aisy, Diva Bilqiis Rihhadatul (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
Product processing from industries is not spared from by-products in the form of wastewater that can contain heavy metals and cause environmental pollution. Chromium (Cr) metal as one of the polluting with difficult-to-decompose, toxic, persistent and bioaccumulative. Activated carbon as an adsorbent obtained from organic waste is one way to reduce heavy metals in wastewater. This study aims to reviewing activated carbon in organic waste such as coconut shells, bagasse, corn cobs, rice husks, pecan shells, salak shells, rubber fruit shells, banana peels, durian peels and acacia pods with the highest effectiveness as adsorbents to reduce of Cr in wastewater. The method was used through searching the literature of journals and research articles in the last 21 years in Indonesian and English using the keywords activated carbon, adsorbents and heavy metals Cr through Google Scholar and Science Direct. 160 articles were obtained relevant to this study and 10 articles were obtained to in the discussion. The results of literature research show that activated carbon in coconut shell organic waste as an adsorbent has a great influence and is able to reduce the concentration of heavy metal chromium (Cr) in 500 ml of textile wastewater by 73.52%.